2014
DOI: 10.1044/2014_jslhr-s-13-0101
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of an Automated High-Resolution Manometry Analysis Program Across Expert Users, Novice Users, and Speech-Language Pathologists

Abstract: Purpose The purpose of this study was to investigate inter- and intra-rater reliability among expert users, novice users, and speech-language pathologists with a semi-automated high-resolution manometry analysis program. We hypothesized that all users would have high intra-rater reliability and high inter-rater reliability. Method Three expert users, 15 novice users, and 5 speech-language pathologists participated in this study. Following a 20-minute training session, users analyzed 30 high-resolution manome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Pressure variability was measured in the following manner: 1) a zero time-point was assigned to the pressure peak on the most superior sensor in the velopharynx for each swallow; 2) pressure waveforms from each sensor were aligned across swallows according to the zero time-point; 3) a coefficient of variation (CV = mean/standard deviation) was calculated on each sensor from the onset to offset of swallowing-related pressure change; 4) CVs were averaged over each sensor in the following regions: velopharynx, mesopharynx, and upper esophageal sphincter; and 5) CVs averaged over each region were summed into a single, overall pressure variability parameter. Reliability analysis was not performed for this study, but we have shown that our methods for extracting HRM measures is reliable between expert users, speech-language pathologists, and undergraduate research assistants [48]. …”
Section: Methodsmentioning
confidence: 99%
“…Pressure variability was measured in the following manner: 1) a zero time-point was assigned to the pressure peak on the most superior sensor in the velopharynx for each swallow; 2) pressure waveforms from each sensor were aligned across swallows according to the zero time-point; 3) a coefficient of variation (CV = mean/standard deviation) was calculated on each sensor from the onset to offset of swallowing-related pressure change; 4) CVs were averaged over each sensor in the following regions: velopharynx, mesopharynx, and upper esophageal sphincter; and 5) CVs averaged over each region were summed into a single, overall pressure variability parameter. Reliability analysis was not performed for this study, but we have shown that our methods for extracting HRM measures is reliable between expert users, speech-language pathologists, and undergraduate research assistants [48]. …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the process of identifying and distinguishing pressures in pharyngeal regions is subjective in nature and may be more difficult when evaluating swallowing pressures in individuals with dysphagia. Nonetheless, our research team has had success in obtaining reliability in evaluating swallowing pressures, both with clinicians knowledgeable about swallowing function and in undergraduate research assistants without prior clinical training [124].…”
Section: Discussionmentioning
confidence: 99%
“…The locations were selected due to reported ease in identification of each region: the UES has a clear band of pressure at rest, and the velopharynx can be identified by non-swallow speech tasks such as production of /kaka/ [77]. These anatomic definitions have been used for measurement in numerous subsequent publications [18,52,63,78,84], and this framework has been adapted in automated analysis programmes described in the literature [91]. …”
Section: Pharyngeal Manometrymentioning
confidence: 99%
“…Research applications of HRM rely heavily on software such as MATLAB to analyse pharyngeal swallowing with custom algorithms outside of commercial HRM devices [78,79,80,81,82,83,91], and reliability of pharyngeal HRM is limited to one study investigating a custom MATLAB programme. The reliability of a custom-designed software programme was evaluated after provision of a 20-min training session to 20 raters with varying experience (e.g., expert and novice speech-language pathologists) [91].…”
Section: Pharyngeal Manometrymentioning
confidence: 99%
See 1 more Smart Citation